Development of a Reusable Front Seat Rig for Enhancing Sustainability in Airbag Testing, A product development project to reduce the number of seats consumed in side airbag testing - Lindholm , Johannes; Viktorsson, Jonathan (My University, 2024)
Physical testing is a necessity in the development of cars today. Regarding safety systems such as the side airbag mounted in the front seat, the test material is currently only used for one test, despite only parts of it being damaged. The quantitative testing performed is thus wasteful. With increased global development and front loading of development projects, the problem is increasingly important. This master thesis covers the development of a front seat rig for airbag testing. The goal was to reduce material waste and thus improve testing activities in terms of cost and sustainability. This report details the process of customer needs elicitation, concept development and design, and evaluation of the proposed rig. To confine the design space, testing of design variable effects on dummy responses was performed and showed that breakthrough material and seat stiffness did not impact dummy results to a large extent. The concept development combined traditional product development methods with model-based methods, such as finite element analysis and topology optimisation. Various solutions were ideated and subsequently screened down to a final solution. After a concept was agreed upon, the detailed design work was performed in iterations with input from senior design and design optimisations performed in Optistruct. The result is a design that fulfils the requirements of durability while being able to cover the full range of motion of the seat, also called a travel box, in an easy manner. The proposed rig could cut testing costs by 86% and reduce the CO2 emissions by 90% measured over 100 tests compared to the current way of testing.
Keywords: Airbag; testing; repetitive; re-usable; rig; occupant safety; SAB; seats; OOP; Out of position